E-Commerce Platform Development as A Means of Increasing Potential MSME Business - Richadinata, Kadek Riyan Putra; Ayuni, Ni Made Sri; Purnamawati, Ni Luh Gede Putu; Widnyani, Ni Made (Global Health Science Group, 2023)
In today's digital era, the presence of technology and innovation is becoming increasingly important for MSMEs to maintain and increase their competitiveness. In the digital era like today, e-commerce is an alternative to overcome these obstacles. However, there are still many MSMEs that have not utilized e-commerce to market their products due to limited access, limited knowledge, and high costs to create their own e-commerce platform. The aim of this research is to find out e-commerce platform development as a means of increasing potential msme business. The research method used in this study is a qualitative research method with a case study approach. This research will be carried out in the following stages: literature study, data collection, data analysis, platform development, and evaluation. This platform was built using responsive website technology so that it can be opened through various platforms connected to the internet. The e-commerce platform contains features such as product catalogs, product orders, payment mechanisms, and shipping processes. Overall the information system is very good, as many as 31 people answered with very good responses.